2022
DOI: 10.48550/arxiv.2207.01051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the minimum number of arcs in $k$-dicritical oriented graphs

Abstract: The dichromatic number χ(D) of a digraph D is the least integer k such that D can be partitionedAn oriented graph is a digraph with no directed cycle of length 2. For integers k and n, we denote by o k (n) the minimum number of edges of a k-critical oriented graph on n vertices (with the convention o k (n) = +∞ if there is no k-dicritical oriented graph of order n). The main result of this paper is a proof that o 3 (n) ≥ 7n+2 3 together with a construction witnessing that o 3 (n) ≤ 5n 2 for all n ≥ 12. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Conjecture 7 has been confirmed for k = 3 by Aboulker et al [2] and for k = 4 by the first and third authors, and Rambaud [16].…”
Section: Contextmentioning
confidence: 64%
See 4 more Smart Citations
“…Conjecture 7 has been confirmed for k = 3 by Aboulker et al [2] and for k = 4 by the first and third authors, and Rambaud [16].…”
Section: Contextmentioning
confidence: 64%
“…Already the minimum number n k of vertices of a k-dicritical oriented graph is unknown except for small values of k : clearly n 2 = 3 ; Neumann Lara [24] proved n 3 = 7 and n 4 = 11 ; Bellitto et al [5] recently established n 5 = 19. As observed by Aboulker et al [2] using a lemma of Hoshino and Kawarabayashi [17], there exists a smallest integer p k such that there exists a k-dicritical oriented graph on n vertices for any n ≥ p k . Moreover, while p 3 = n 3 = 7, they showed that p 4 = n 4 because there is no 4-dicritical oriented graph on 12 vertices.…”
Section: Contextmentioning
confidence: 84%
See 3 more Smart Citations